Analisis Kerusakan Jalan Perkerasan Lentur menggunakan Metode Pavement Condition Index (PCI): Analisis Kerusakan Jalan Menggunakan Metode Pavement condition index (PCI) - Wira Kesuma Putra Wira; Ade Nurdin ade; Fetty Ferbriasti fetty (JURNAL TEKNIK, 2022)
Overall condition of the East Ring Road I, Kec. Paalmerah Jambi City, which suffered light, moderate, or heavy damage in several segments, the East Ring Road I, Kec. Paalmerah Jambi City is a primary arterial road with national road status and based on its location in an urban 2/2 road type, and also the East Ring Road I is a connecting road to the Talang Duku port where vehicles pass through the road with or without load, the East Ring Road I there are several offices and warehouses, you could say the area is an industrial area. on these roads there is damage that interferes with the comfort of drivers where damage to this segment can interfere with the activities of road users so that it can affect vehicle travel time to be slow. on these roads there is damage that interferes with the comfort of drivers where damage to this segment can interfere with the activities of road users so that it can affect vehicle travel time to be slow. Within a few years of being born there is quite a lot of damage at some point, Type of Damage. As a result disturbing comfort in driving and even accidents . The results of the analysis of road damage using the PCI method obtained a PCI value of 67,333 with good pavement conditions. Based on the graph of the relationship between the level of road damage and speed, it can be concluded that the higher the level of damage, the lower the PCI value and will affect the slow speed of the vehicle. On the other hand, the higher the PCI value, the lower the damage rate and the faster the vehicle speed.